Analysis of PM10 trends in open-pit mining: Assessing emission controls and WHO guideline compliance - Roberto Rojano; Heli A. Arregocés; Gloria Restrepo (Heliyon)
This study evaluated the concentrations, trends, and variability of PM10 particulate matter in two Air Quality Monitoring Systems (CorpoGuajira's_AQMS and Cerrejón's_AQMS) in an open-pit coal mine in northeastern Colombia from 2010 to 2020. Additionally, different levels of emission controls were evaluated to achieve compliance with Colombian standards and international WHO guidelines. The results showed concentrations ranging from 24.14 μg/m3 to 46.46 μg/m3 in CorpoGuajira's_AQMS and 18.36 μg/m3 to 46.83 μg/m3 in Cerrejón's_AQMS. The concentrations of PM10 at all the stations studied exceed the most recent annual guidelines of the World Health Organization (15 μg/m3); in contrast, the concentrations were below the PM10 annual levels established in the Colombian standards (50 μg/m3). The TheilSen function of R was used to explore the temporal variability of PM10 during 2010–2020. All stations located near mining operations and downwind of the mining showed a significant trend of increasing PM10 concentrations (p < 0.05). During the study period, we analyzed monthly data on temperature, relative humidity, precipitation, wind speed, and wind direction. Meteorological parameters showed no significant anomalies with yearly values for the region. The results showed that without control measures, the concentrations at the stations in the center and south of the mine would increase to 67.50 % (76.36 μg/m3) and 40.50 % (67.47 μg/m3), respectively. In this context, emission controls need to be established at 80 % to comply with the 24-h guidelines of WHO (45 μg/m3) and 59 % to comply with the daily levels established in Colombia (75 μg/m3). The station located upwind of the mining activity was affected by regional sources of PM10. In order to comply with Colombian daily standards and WHO daily guidelines, regional sources must reduce their emissions by approximately 60 %. These results underscore the importance of considering control measures in the planning of mining activities and highlight the need to incorporate these observations to comply with national and international standards.